Frequency of renal tubular acidosis in children with down syndrome - Puente, Silvestre García de la; Arizmendi, Karla Adney Flores; Villegas, Junior Rafael Gahona; Genoy, Paola Andrea Yepes; Guerrero, Elena Lissette Garza (Journal of Clinical Nephrology, 2020)
Background: Down syndrome (DS) is associated with various congenital diseases and malformations, including those of the kidneys and urinary tract. It has been thought that renal tubular acidosis (RTA) is more frequent in this population. The objective of this study was to assess the frequency of RTA and, secondarily, of other renal and urological disorders in persons with DS. Method: An observational, ambispective, descriptive and cross-sectional study of patients diagnosed with RTA, or suspected kidney or urological disorders, was carried out from July 2016 to September 2017 at the Down syndrome clinic of the Mexican National Institute of Paediatrics. Urinalysis was performed, along with analyses of venous blood gas, sodium, potassium, chlorine, calcium, phosphorus, albumin and creatinine. Those with any abnormal values were referred to nephrology for diagnostic evaluation. Results: Of a total of 700 patients seen at the clinic, 47 met the selection criteria. Of these, 32 had no RTA or other renal or urological alterations. The remaining 15 continued to the second phase of the study, where 6 were diagnosed with nephropathy or uropathy (RTA, systemic arterial hypertension, monosymptomatic familial haematuria, mild renal failure secondary to reflux nephropathy, urinary tract infection or right ureteropelvic stenosis). Four had mild metabolic acidosis without meeting the criteria for diagnosis of RTA. Conclusion: RTA is not more common in children with Down syndrome. Nephropathies and uropathies should be investigated in the evaluation of DS patients.